CONTRIBUTION TO THE STUDY OF ZIRCONIUM AND HAFNIUM ALPHA-HYDROXYCARBOXYLATES - Barbieri, R. S.; Terra, V. R.; Netto, A. M.; Rocha, J. C. (Soc Brasileira Quimica, 1995)
A study of both zirconium and hafnium alpha-hydroxycarboxylates for analytical applications is presented, These compounds are studied by infrared spectroscopy, thermal analysis and X-ray diffractometry. dl-Mandelic, dl-p-bromomandelic and dl-2-naphthylglycolic acids are the more adequate reagents for gravimetric determinations of zirconium and hafnium, the ligands dl-2-hydroxyhexanoic and dl-2-hydroxydodecanoic acids were used for the first time and the results showed that they are also adequate reagents for the same purpose.
Keywords: ZIRCONIUM ALPHA-HYDROXYCARBOXYLATES; HAFNIUM ALPHA-HYDROXYCARBOXYLATES; ZIRCONIUM GRAVIMETRY; HAFNIUM GRAVIMETRY